Effect of oodev and turmeric powder dietary supplementations on the reproductive performance of sunset platy fish Xiphophorus maculatus - Harton Arfah; Odang Carman; Muhamad Fathurrizki Darmawan; Fajar Maulana; Lina Mulyani (Jurnal Akuakultur Indonesia)
Plati fish is a freshwater ornamental fish with great demand  due to its beautiful body shape and color, besides the price is affordable.The main problem faced by plati fish farmers is that the production targets have not been achieved to meet the market needs. This study aimed to examine the effect of the oodev and turmeric powder and the combination of both added into the fish diet on the reproductive performance of plati fish broodstock. The experimental design in this study used a completely randomized design with four treatments, i.e treatment A (control), B (oodev 0.5 ml/kg broodstock), C (turmeric powder 3%/kg feed), and D (oodev 0.5 ml/kg broodstock + turmeric powder 3%/kg feed). There were three replications for each treatment. The observed parameters included the percentage of pregnant broodstocks, the percentage of labored broodstocks, the frequency of labored broodstocks, larvae production, and the survival rate of the larvae. The data were analyzed using ANOVA and further tested with Duncan's test with a 95% confidence level. The results showed that the addition of oodev, turmeric flour, and a combination of both into the feed every one week increased the average production of larvae. Total larval production in all treatments was sorted from the highest in treatment D, B, C, and and the lowest was A treatment with larvae production of 428, 251, 209, and 93, respectively. The addition of oodev 0.5 ml/kg broodstock, turmeric powder 3%/kg feed, and the combination of both into the feed increased larval production three, two, and five times higher compared to the control, respectively. The percentage of survival of the larvae is sorted from the highest in treatment D, B, C, A, i.e. 97.51%, 95.79%, 95.65%, and 93.32%, respectively.